2021
DOI: 10.1111/pbi.13702
|View full text |Cite
|
Sign up to set email alerts
|

RGN1 controls grain number and shapes panicle architecture in rice

Abstract: Summary Yield in rice is determined mainly by panicle architecture. Using map‐based cloning, we identified an R2R3 MYB transcription factor REGULATOR OF GRAIN NUMBER1 (RGN1) affecting grain number and panicle architecture. Mutation of RGN1 caused an absence of lateral grains on secondary branches. We demonstrated that RGN1 controls lateral grain formation by regulation of LONELY GUY (LOG) expression, thus controlling grain number and shaping panicle architecture. A novel favourable allele, RGN1C, derived from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 54 publications
(66 reference statements)
0
25
0
Order By: Relevance
“…OsLOG expression was downregulated in rgn1-1 and NIL-rgn1 compared with japonica cultivar Nipponbare and NIL-RGN1 (Table 1), whereas the expression of LOG in RGN1-OE3 plants was upregulated. Moreover, yeast one-hybrid assays showed that RGN1 bound directly to the promoter region of OsLOG, and overexpression of OsLOG from Nipponbare in BS208 partially rescued the absence of lateral grains in secondary branches (Table 1), leading Li et al (2021) to the conclusion that RGN1 affects lateral grain number and panicle architecture in rice by regulation of OsLOG expression.…”
Section: Reproductive Tissuesmentioning
confidence: 97%
See 4 more Smart Citations
“…OsLOG expression was downregulated in rgn1-1 and NIL-rgn1 compared with japonica cultivar Nipponbare and NIL-RGN1 (Table 1), whereas the expression of LOG in RGN1-OE3 plants was upregulated. Moreover, yeast one-hybrid assays showed that RGN1 bound directly to the promoter region of OsLOG, and overexpression of OsLOG from Nipponbare in BS208 partially rescued the absence of lateral grains in secondary branches (Table 1), leading Li et al (2021) to the conclusion that RGN1 affects lateral grain number and panicle architecture in rice by regulation of OsLOG expression.…”
Section: Reproductive Tissuesmentioning
confidence: 97%
“…We located three putative wheat RGN1 sequences in the NCBI database, most likely associated with the A, B and D sub-genomes. This sequence is highly conserved in Aegilops tauschii (the progenitor of the D genome of bread wheat; Li et al, 2021) and is conserved in the first half of the RGN1 sequence in wheat (Table S4). Additionally, promoter motif scanning analysis showed that all 37 TaLOG GFMs have the highly conserved motif, ACCAAA (located at the end of the 18 th motif of Figure S9), which was shown by Li et al (2021) to be bound by OsRGN1.…”
Section: Reproductive Tissuesmentioning
confidence: 99%
See 3 more Smart Citations